Digital tools towards transplant first policy: Improving health literacy - Daniela R. Nogueira; Manuela Almeida; Anabela S. Rodrigues (Publicações Ciência e Vida, 2021)
End stage kidney disease (ESKD) is a prevalent health issue across the world and it is well established that kidney transplantation (KT), specifically from a living donor, is currently the best value-based treatment method. Ergo, it is crucial to invest heavily in making this care strategy the best possible option for the majority of eligible patients. Barriers to the kidney transplant process are mainly related to education and accessibility: awareness of the clinical and societal relevance of the therapy must be promoted at the level of patients, clinicians and health providers. A health-literacy-focused website has been developed as part of this, aiming to provide the general population, particularly potential organ receptors and donors, with better access to trustworthy information and data. This was meant to be the effective expression of knowledge diffusion and innovation as a result of an academic master thesis. This communication-focused digital resource is designed to combat these obstacles and to create a long-lasting, positive and significant impact.